Sistematización de experiencias de gestión documental para la legalización de matrículas en la secretaría académica de la Facultad De Ciencias de la Ingeniería y Aplicadas de la Universidad Técnica de Cotopaxi - Lema Satuquinga, Fátima Elizabeth (2019)
The systematization of experiences were focused directly on legalization process of second and third enrollment to contribute with knowledge relationated to document management to improve the organization and classification of them, guaranteeing availability and access to the files, which had as an object to identify its classification systems for documents conservation, taking into account documentary series types, techniques and norms that allow to maintain the uniformity over information handling at legalization processes of second and third enrollments on Academic Secretariat of ¬ CIYA Faculty, that means, the document is authentic within the legal framework according to the institution Academic Regulations. In this way the selection of the object was made observing legalization process practice of second and third registration where the organization and management of archiving techniques was visualized when documents were classifyed and organized. With sought experience evidence were left through a diagnosis about enrollments process strengthening at this dependence. Finally, the working team recommends the use of alphanumeric file system, since it will provide to the agency documents location and identification fastlly and on time, allowing easy access to information, speeding up legalization process of second and third matricules.